2008
DOI: 10.1167/iovs.07-0557
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification Does Not Induce Neovascular Age-Related Macular Degeneration

Abstract: The results indicate that cataract surgery in eyes with early AMD is not a causative factor in neovascular AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 27 publications
3
50
0
3
Order By: Relevance
“…7 It has been recommended that indications for cataract surgery should be more stringent than at present, in particular for patients with signs indicating a high risk for progression to late AMD. On the other hand, some studies 3, [8][9][10] could not confirm such observations. Nevertheless, several studies 11,12 report sustained improvement in visual function after cataract surgery in patients with early AMD.…”
mentioning
confidence: 89%
“…7 It has been recommended that indications for cataract surgery should be more stringent than at present, in particular for patients with signs indicating a high risk for progression to late AMD. On the other hand, some studies 3, [8][9][10] could not confirm such observations. Nevertheless, several studies 11,12 report sustained improvement in visual function after cataract surgery in patients with early AMD.…”
mentioning
confidence: 89%
“…58 Recent large studies including a report from the multi-centre Age-related Eye Diseases Study (AREDS), which included 8,050 eyes, have found no significant evidence to Complications of cataract surgery Chan, Mahroo and Spalton support this. 59,60 Some cases of neovascular age-related macular degeneration are amenable to timely treatment with anti-VEGF agents and therefore, accurate diagnosis is important, so that there is no delay in treatment. One report 61 found a high incidence of neovascular age-related macular degeneration at one week after cataract surgery, suggesting that this was present pre-operatively, but was missed due to lens opacity.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…More recently, studies published have not showed an increase in recurrence, number of injections or worsening of visual acuity when compared with non-operated eyes [15,16,[25][26][27][39][40][41][42][43][50][51][52][53][54][55][56]. However, Lee and cols.…”
Section: Neovascular Amdmentioning
confidence: 99%
“…The studies published about cataract surgery in patients with neovascular AMD are mainly retrospective, FAG was only performed as a diagnostic test and not on the follow-up; some of them without control group and with short periods of follow-up [15,16,[25][26][27][39][40][41][42][43][50][51][52][53][54][55]58]. In addition, the protocols used in the reported studies, were inhomogeneous (treat and extend, pro-re-nata and monthly injections), but none compared these protocols between them, or even between different anti-VEGF agents (bevacizumab, ranibizumab or aflibercept) [38,39,[41][42][43][52][53][54][55].…”
Section: Neovascular Amdmentioning
confidence: 99%
See 1 more Smart Citation